Oxidative stress associated with rapid weight reduction decreases circulating adiponectin concentrations - Yanagawa, Y.; Morimura, T.; Tsunekawa, K.; Seki, K.; Ogiwara, T.; Kotajima, N.; Machida, T.; Matsumoto, S.; Adachi, T.; Murakami, M. (Endocrine Journal, 2010)
The effect of stress associated with acute weight reduction on adipocytokine production is incompletely understood. In the present study, we have investigated the changes in circulating adipocytokine concentrations and urinary concentrations of stress markers in male collegiate wrestlers during acute weight reduction for a competition. Twenty healthy Japanese male wrestlers (18-22 years of age) who participated in the national collegiate wrestling tournament were studied. Body weight, body fat amount, serum testosterone, serum leptin, serum adiponectin, urinary 8-hydroxy-2`- deoxyguanosine (8-OHdG) and urinary biopyrrins were analyzed during acute weight reduction for the competition. Body weight, body fat amount and the serum concentrations of testosterone, leptin and adiponectin significantly decreased on the day of weigh-in compared with the levels 12 days before weigh-in. In contrast, urinary concentrations of 8-OHdG and biopyrrins significantly increased on the day of weigh-in compared with the concentrations 12 days before weigh-in. A positive correlation was observed between the serum concentrations of adiponectin and testosterone, and a negative correlation was observed between the concentrations of serum adiponectin and urinary biopyrrins. The present results suggest that rapid weight reduction increases the urinary concentrations of stress markers, which is associated with a decrease in serum concentrations of adiponectin.